High-strength low-warpage lithium aluminum silicate glass and preparation method thereof

By using SO2 atmosphere annealing treatment and chemical strengthening method in the float glass molding process, the problem of high warpage of lithium aluminosilicate glass is solved, significantly improving its mechanical strength and surface compressive stress uniformity, and achieving high strength low Warped glass preparation.

CN119306380APending Publication Date: 2025-01-14SICHUAN HONGKE INNOVATION TECH CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411439047.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-15
Publication Date
2025-01-14

AI Technical Summary

Technical Problem

The float glass molding process leads to different chemical compositions of the tin surface and the non-tin surface, which affects the mechanical strength and warpage of the glass. It is difficult for the prior art to effectively improve warpage and improve strength.

Method used

Annealing was performed under an atmosphere containing SO2 to control the change ratio of Na2O, and the mechanical strength of lithium aluminosilicate glass was increased and warpage was reduced by chemical strengthening.

Benefits of technology

Through annealing treatment and chemical strengthening, the mechanical strength of lithium aluminosilicate glass is significantly improved, and the warpage is controlled below 0.14%, ensuring the uniformity of the surface compressive stress distribution of the glass and the glass performance after chemical strengthening.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005085866840000101
    Figure BDA0005085866840000101
  • Figure BDA0005085866840000111
    Figure BDA0005085866840000111
  • Figure BDA0005085866840000121
    Figure BDA0005085866840000121
Patent Text Reader

Abstract

The invention relates to the field of glass manufacturing, and particularly discloses high-strength low-warpage lithium aluminum silicate glass and a preparation method thereof. The preparation method comprises the following steps: carrying out annealing treatment on a float glass substrate in an atmosphere containing SO2 to obtain lithium aluminosilicate body glass, and then carrying out chemical strengthening; in the annealing treatment process, the volume concentration of SO2 is 96%-100%, the outlet temperature of SO2 is 30-80 DEG C, and the variation of Na2O in the non-tin surface and the tin surface of the aluminosilicate body glass meets the condition that alpha (Na2O) / beta (Na2O) = (1.08-1.28): 1. According to the method, the annealing process is improved to ensure that the chemical components of the tin surface and the non-tin surface tend to be consistent, so that the problem of high warping rate of the lithium aluminosilicate glass subjected to chemical strengthening treatment is prevented, and the warping rate of the finally obtained lithium aluminosilicate glass is less than 0.14%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of glass manufacturing, and more specifically, to a high-strength, low-warp lithium aluminosilicate glass and a preparation method thereof. Background Art

[0002] With the continuous development of smart electronic product technology, the large-screen, light-weight and thinner mobile touch smart devices such as smartphones and tablets have become a new trend. The production process of lithium aluminum silicate glass adopts the float production process. Float glass is named because the molten glass floats on the surface of molten tin to form flat glass. This production method does not need to overcome the gravity of the glass itself, so the width of the original glass plate can be increased, the pulling speed can be greatly improved, and the output and production scale can be increased; and because the molding is carried out on the surface of the molten metal liquid, high-quality mirror glass with double-sided fire polishing can be obtained.

[0003] The process of float glass forming is that the high-quality glass liquid from the tank kiln after melting, clarifying and cooling floats on the surface of the molten tin liquid in the tin bath, and completes the processes of flattening, thinning, polishing, cooling and solidification, becoming high-quality ultra-thin electronic glass that is superior to polished glass. Since the entire process is completed on the surface of the tin liquid, and one side is in contact with the tin liquid, called the tin side; the other side is in contact with the air, called the non-tin side, but this process method inevitably causes the molten tin ions to diffuse to the lower surface of the glass, and the final glass product will have different chemical compositions on the tin side and the non-tin side.

[0004] Since the chemical composition of the tin side and the non-tin side of the glass is inconsistent, the ion exchange rate of the glass during the chemical strengthening process will be further affected, resulting in uneven stress distribution on the upper and lower surfaces of the glass and warping. The warping may lead to local stress concentration in the glass, thereby reducing its overall strength. Therefore, how to improve the warping of float glass and improve its mechanical strength is a technical problem that needs to be solved urgently in this field. Summary of the invention

[0005] In order to improve the warpage of float glass and enhance the mechanical strength, the present application provides a high-strength and low-warpage lithium aluminum silicate glass and a preparation method thereof.

[0006] This application adopts the following technical solutions:

[0007] In a first aspect, the present application provides a method for preparing high-strength and low-warpage lithium aluminosilicate glass, comprising:

[0008] A glass substrate is obtained by a float glass forming process, the glass substrate is annealed in an atmosphere containing SO2 to obtain a lithium aluminum silicate main body glass, and the lithium aluminum silicate main body glass is chemically strengthened;

[0009] During the annealing process, the volume concentration of SO2 is 96% to 100%, the outlet temperature of SO2 is 30°C to 80°C, and the change in the amount of Na2O in the non-tin surface of the aluminosilicate body glass is △ α (Na2O), the change in the amount of Na2O in the tin surface is △ β (Na2O), both satisfy:

[0010] △ α (Na2O) / △ β (Na2O) = (1.08-1.28): 1

[0011] The warpage rate of the lithium aluminosilicate glass finally obtained is less than 0.14%.

[0012] Furthermore, during the annealing process, the non-tin surface of the aluminosilicate main glass faces the SO2 vent hole, and the flow rate of the SO2 is 6 L / min to 90 L / min.

[0013] Furthermore, during the annealing process, the distance between the aluminosilicate main glass and the vent hole of SO2 is 15-20 mm, and the diameter of the vent hole is 0.2-0.4 mm.

[0014] Furthermore, during the above annealing process, 6 to 10 SO2 ventilation pipes are arranged in the annealing kiln, each SO2 pipe is provided with a temperature control system, a flow meter and a plurality of ventilation holes, and the center distance between two adjacent ventilation holes is 12 to 18 mm.

[0015] Furthermore, the temperature of the annealing treatment is 430°C to 710°C.

[0016] Furthermore, during the annealing process, the temperature in the annealing furnace changes gradually in the range of 430°C to 710°C.

[0017] Furthermore, during the above annealing process, the glass substrate passes through a high temperature zone, a medium temperature zone and a low temperature zone at a uniform speed;

[0018] The initial temperature of the high temperature zone is 680-710°C and the final temperature is 610-630°C;

[0019] The initial temperature of the medium temperature zone is 610-630°C, and the final temperature is 510-530°C;

[0020] The initial temperature of the low temperature zone is 510-530°C, and the final temperature is 430-450°C.

[0021] Furthermore, the raw materials of the glass matrix include, by mass percentage:

[0022] 61.5% to 63.2% SiO2, 19% to 20.5% Al2O3, 6.8% to 7.5% Na2O, 1.2% to 1.5% K2O, 4.2% to 4.8% Li2O, 2.6% to 3.2% MgO, 2.2% to 2.6% ZrO2.

[0023] Furthermore, the above chemical strengthening is a two-step strengthening method, including:

[0024] In the first chemical strengthening, the molten salt is pure NaNO3, the strengthening temperature is 430-450℃, and the strengthening time is 70-90min.

[0025] For the second chemical strengthening, the molten salt is a mixed molten salt composed of 1.5-2.5wt% NaNO3 and 97.5-98.5wt%, the strengthening temperature is 410-430°C, and the strengthening time is 80-100min.

[0026] In a second aspect, the present application provides a high-strength, low-warpage lithium aluminosilicate glass, which is prepared by the above-mentioned preparation method; the warpage of the lithium aluminosilicate glass is less than 0.14%, the surface CS of the lithium aluminosilicate glass is greater than 950Mpa, and the surface DOL is greater than 110μm; the intact rate of the lithium aluminosilicate glass dropped from a height of at least 160cm onto the surface of 180-mesh silicon carbide sandpaper is greater than 82%.

[0027] In summary, this application has the following beneficial effects:

[0028] The glass substrate obtained by the float glass forming process of the present application is completed on the surface of the tin liquid throughout the process. The molten tin ions easily diffuse to the lower surface of the glass, resulting in different chemical compositions of the tin surface and the non-tin surface of the glass product. The present application improves the annealing process so that the glass substrate is annealed in an atmosphere containing SO2, so that the Na2O on the surface of the lithium aluminum silicate glass reacts chemically under the action of acidic SO2 to form Na2SO3 or Na2 SO4. In this way, the change amount of Na2O on the non-tin surface can be controlled. α (Na2O) and the change of tin surface△ β (Na2O) is (1.08-1.28), which ensures that the chemical composition of the tin surface and the non-tin surface is consistent, so that the ion exchange rate and the total amount of ion exchange of the lithium aluminum silicate glass during the chemical strengthening process are also consistent, thereby preventing the problem of high warpage of the lithium aluminum silicate glass after chemical strengthening. After annealing and chemical tempering, the mechanical strength of the lithium aluminum silicate glass is significantly improved, the surface compressive stress distribution is relatively uniform, and the warpage is stably controlled below 0.14%. DETAILED DESCRIPTION

[0029] The embodiments of the present invention will be described in detail below in conjunction with examples. However, those skilled in the art will understand that the following examples are only used to illustrate the present invention and should not be construed as limiting the scope of the present invention. The specific conditions not specified in the examples are carried out according to conventional conditions or conditions recommended by the manufacturer. The reagents or instruments used without indicating the manufacturer are all conventional products that can be purchased commercially.

[0030] The technical solution of the present invention is:

[0031] This embodiment provides a method for preparing high-strength and low-warpage lithium aluminosilicate glass, which comprises the following steps:

[0032] Step S1: obtaining a glass substrate by a float glass forming process.

[0033] In the process of preparing the glass matrix, raw materials containing SiO2, Al2O3, Na2O, K2O, Li2O, MgO, and ZrO2 are added with glass powder and clarifier to prepare the finished batch. The finished batch is then sent to the pool for heating to completely melt it into glass liquid, and after the clarification and homogenization process, the bubbles and impurities in the glass liquid are removed, and the composition and temperature of the glass liquid are made uniform. Then the molten glass liquid flows out of the melting furnace and flows into the tin bath through the guide trough. The tin bath is filled with molten tin liquid, and its density is greater than that of the glass liquid, so that the glass liquid can float on the surface of the tin liquid. Under the action of gravity and surface tension, the glass liquid is naturally flattened on the surface of the tin liquid, and a glass ribbon with flat upper and lower surfaces and uniform thickness is formed. The glass ribbon gradually hardens and cools on the tin liquid to achieve sufficient strength and stability to obtain a glass matrix.

[0034] Furthermore, in a preferred embodiment of the present application, the raw materials of the glass matrix include, by mass percentage:

[0035] 61.5% to 63.2% SiO2, 19% to 20.5% Al2O3, 6.8% to 7.5% Na2O, 1.2% to 1.5% K2O, 4.2% to 4.8% Li2O, 2.6% to 3.2% MgO, 2.2% to 2.6% ZrO2.

[0036] Preferably, the raw materials of the above-mentioned glass matrix include, by mass percentage, 62.0% to 62.8% SiO2, 19.5% to 20.3% Al2O3, 7.1% to 7.3% Na2O, 1.3% to 1.4% K2O, 4.3% to 4.6% Li2O, 2.8% to 3.0% MgO, and 2.3% to 2.5% ZrO2.

[0037] By using the above raw materials in percentage by mass and in a reasonable ratio, the float glass can have a stronger ion exchange capacity, a larger depth of the ion exchange layer can be formed after chemical strengthening, and a higher surface compressive stress can be generated.

[0038] Step S2: annealing the glass substrate in an atmosphere containing SO2 to obtain a lithium aluminosilicate main body glass. During the annealing process, the volume concentration of SO2 is 96% to 100%, the outlet temperature of SO2 is 30°C to 80°C, and the change amount of Na2O in the non-tin surface of the aluminosilicate main body glass is △ α (Na2O), the change in the amount of Na2O in the tin surface is △ β (Na2O), both satisfy:

[0039] △ α (Na2O) / △ β (Na2O)=(1.08~1.28):1.

[0040] Preferably, both satisfy: α (Na2O) / △ β (Na2O)=(1.1~1.2):1.

[0041] The formed glass matrix enters the annealing kiln for slow cooling. The annealing process can eliminate the thermal stress inside the glass, improve its mechanical properties and stability, and prevent cracking during subsequent processing or use.

[0042] The inventors have found that the warping of float glass is mainly caused by:

[0043] During the float glass forming process, the amount of tin infiltration on the upper and lower surfaces of the glass is different. The mass fraction of tin oxide on the lower surface is about 2%, and the penetration depth is 10-30μm, with a characteristic peak on the depth distribution curve; the mass fraction of tin oxide on the upper surface is about 0.1%, and its characteristic peak is only 1% of the lower surface. The tin oxide that infiltrates the glass mainly exists in the form of stannous oxide. Studies have shown that Sn 2+ Accounting for 80% of the total tin infiltration amount, Sn 4+ Accounts for 20%, and Sn on the glass surface at 0-1.5μm 4+ Higher contents are related to oxidation during annealing.

[0044] The inventors have found that the distribution of tin infiltration on the surface of float glass is related to its process. In the tin bath, the diffusion of tin into the glass follows the general diffusion principle. During the annealing process after the glass leaves the tin bath, when it is treated with SO2, Sn 2+ Oxidized to Sn 4+ According to the network matching principle, Sn 4+It is easy to diffuse into the interior of the glass to form a satellite peak. At this time, the tin content on the glass surface will decrease. The ratio of the reduced value (measured value) CE0 to the value before treatment C0 (theoretical value obtained by fitting using the diffusion principle) is called the treatment factor ξ. The treatment factor ξ reflects the ability of the SO2 annealing process to reduce the tin content C0 on the glass surface. The larger the ξ value, the stronger the ability to reduce the surface tin content.

[0045] In the present application, lithium aluminum silicate glass is annealed in an atmosphere containing SO2, so that the Na2O on the surface of the lithium aluminum silicate glass undergoes a chemical reaction under the action of acidic SO2 to form Na2SO3 or Na2 SO4. And by controlling the concentration and temperature of SO2, the change amount of Na2O on the non-tin surface is controlled. α (Na2O) and the change of Na2O on the tin surface△ β The ratio between the two can ensure that the composition of the tin surface and the non-tin surface is consistent, and the ion exchange rate and the total amount of ion exchange during the chemical strengthening process are also consistent, thereby preventing the problem of high warpage of lithium aluminum silicate glass after chemical strengthening. After annealing and chemical tempering, the mechanical strength of lithium aluminum silicate glass is significantly improved, the surface compressive stress distribution is relatively uniform, and the warpage is stably controlled below 0.14%.

[0046] Among them, △ α (Na2O) and β (Na2O) can be obtained by testing the Na2O content of the non-tin surface, inner layer and tin surface of the lithium aluminum silicate body glass by X-ray fluorescence spectrometer. When testing the Na2O content of the inner layer, the lithium aluminum silicate body glass needs to be double-sided polished and ground to reduce the thickness of each side by 0.02mm. α (Na2O) is the Na2O content of the inner layer minus the Na2O content of the non-tin surface, and the △ β (Na2O) is the Na2O content of the inner layer minus the Na2O content of the tin surface.

[0047] Furthermore, in order to better control △ α (Na2O) and △ β (Na2O) ratio, this application optimizes the SO2 atmosphere conditions during annealing:

[0048] During the annealing process, the volume concentration of SO2 is 96% to 100% (preferably above 97%); the outlet temperature of SO2 is 30°C to 80°C (preferably 40°C to 70°C); the flow rate of SO2 is 6L / min to 90L / min (preferably 10L / min to 80L / min). The SO2 atmosphere under such conditions can promote the reaction between SO2 and components in the glass at the annealing temperature. The generation and distribution of the reaction products will affect the uniformity and surface tension of the glass, thereby affecting the warping of the glass.

[0049] Furthermore, in order to obtain better results in improving warping, the present application controls the SO2 atmosphere through the following parameters: the distance between the aluminosilicate main glass and the SO2 vent is 15 to 20 mm (preferably 16-19 mm), and the diameter of the vent is 0.2 to 0.4 mm (0.25-0.35 mm); during the annealing process, 6 to 10 SO2 ventilation pipes are arranged in the annealing furnace, each SO2 pipe is provided with a temperature control system, a flow meter and a plurality of vents, and the center distance between two adjacent vents is 12 to 18 mm (preferably 14-16).

[0050] Furthermore, the temperature of the above annealing treatment is 430℃~710℃. During the annealing treatment, the temperature in the annealing furnace changes gradually in the range of 430℃~710℃, and the glass matrix passes through the high temperature zone, the medium temperature zone and the low temperature zone at a uniform speed; wherein, the initial temperature of the high temperature zone is 680~710℃, and the terminal temperature is 610~630℃; the initial temperature of the medium temperature zone is 610~630℃, and the terminal temperature is 510~530℃; the initial temperature of the low temperature zone is 510~530℃, and the terminal temperature is 430~450℃. The temperature curve of annealing has a significant effect on the warping of the glass. The temperature gradient change after the optimization of the present application is moderate, which helps to eliminate the internal stress of the glass, ensure that the glass can be evenly heated and cooled during the annealing process, and prevent warping.

[0051] Step S3: chemically strengthening the lithium aluminum silicate glass.

[0052] Furthermore, the above chemical strengthening is a two-step strengthening method, including:

[0053] For the first chemical strengthening, the molten salt is pure NaNO3, the strengthening temperature is 430-450°C, and the strengthening time is 70-90 min; preferably, the molten salt is pure NaNO3, the strengthening temperature is 435-445°C, and the strengthening time is 75-85 min;

[0054] For the second chemical strengthening, the molten salt is a mixed molten salt composed of 1.5-2.5wt% NaNO3 and 97.5-98.5wt%, the strengthening temperature is 410-430°C, and the strengthening time is 80-100min. Preferably, the molten salt is a mixed molten salt composed of 1.7-2.3wt% NaNO3 and 97.7-98.3wt%, the strengthening temperature is 415-425°C, and the strengthening time is 85-95min.

[0055] The specific embodiments of the present invention are described in detail below. It should be understood that the specific embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.

[0056] Example 1

[0057] This embodiment provides a high-strength and low-warpage lithium aluminum silicate glass, and a preparation method thereof comprises the following steps:

[0058] (1) Prepare materials according to the mass ratio of each oxide in Table 1, and add cullet powder and clarifier to prepare a finished batch material. Melt, clarify and shape the finished batch material to obtain a glass matrix;

[0059] (2) The glass substrate is sent into an annealing furnace, wherein 8 SO2 pipes are arranged in the annealing furnace, and the distance between the SO2 pipes and the initial aluminosilicate glass is 18 mm; the SO2 pipes are provided with a temperature control system, a flow meter and a vent hole, the diameter of the vent hole is 0.3 mm, and the center distance of the vent hole is 15 mm. The non-tin surface of the glass faces the vent hole, and the initial thickness of the glass substrate is 0.6 mm. The temperature of SO2 is 30°C, the flow rate is 6L / min, and the volume concentration is 96%. The glass substrate is annealed at a uniform speed through a high temperature zone, a medium temperature zone and a low temperature zone, and the temperature of the high temperature zone is reduced from 700°C to 620°C, the temperature of the medium temperature zone is reduced from 620°C to 520°C, and the temperature of the low temperature zone is reduced from 520°C to 440°C.

[0060] (3) After the lithium aluminum silicate glass is subjected to a gradient temperature preheating treatment, it is placed in a molten salt for two wet ion exchanges. The first chemical strengthening salt bath is 100% NaNO3, and the strengthening conditions are: 440°C, 80 min; the second chemical strengthening salt bath is a mixed salt of 98% KNO3 and 2% NaNO3, and the strengthening conditions are: 420°C, 90 min, to obtain a high-strength and low-warpage lithium aluminum silicate glass.

[0061] Examples 2-6 and Comparative Examples 1-4

[0062] The difference between this group of examples and comparative examples and Example 1 is that the mass ratios of the oxides in the glass are different, as shown in Table 1.

[0063] Table 1.

[0064] serial number <![CDATA[SiO2]]> <![CDATA[Al2O3]]> <![CDATA[Na2O]]> <![CDATA[K2O]]> MgO <![CDATA[Li2O]]> <![CDATA[ZrO2]]> Example 1 62.0 19.8 7.0 1.2 2.8 4.8 2.4 Example 2 63.2 19.7 6.8 1.3 2.6 4.2 2.2 Example 3 61.5 20.5 7.0 1.4 2.8 4.4 2.4 Example 4 61.9 19.0 7.5 1.5 3.2 4.3 2.6 Example 5 61.7 20.1 7.2 1.4 2.8 4.5 2.3 Example 6 62.3 19.5 6.9 1.3 3.0 4.6 2.4 Comparative Example 1 60.5 17.0 8.6 4.5 4.0 2.2 3.2 Comparative Example 2 59.8 18.2 4.0 8.2 5.5 3.2 1.1 Comparative Example 3 64.1 16.5 8.1 0.9 6.6 1.2 2.6 Comparative Example 4 61.0 15.9 8.1 3.2 7.6 2.8 1.4

[0065] Examples 7-12 and Comparative Examples 5-9

[0066] The difference between this group of embodiments and comparative examples and embodiment 1 is that the condition parameters of SO2 in the annealing step are different, as shown in Table 2.

[0067] Table 2.

[0068]

[0069]

[0070] Examples 13-14

[0071] The difference between this group of embodiments and embodiment 1 is that the setting of the SO2 atmosphere in the annealing furnace in the annealing step is different, as follows:

[0072] Example 13: Six SO2 pipes are provided in the annealing furnace, and the distance between the SO2 pipes and the initial aluminosilicate glass is 20 mm; the SO2 pipes are provided with a temperature control system, a flow meter and vents, the diameter of the vents is 0.4 mm, and the center distance of the vents is 18 mm. The non-tin surface of the glass faces the vents, and the initial thickness of the glass substrate is 0.6 mm.

[0073] Example 14: 10 SO2 pipes are arranged in the annealing furnace, and the distance between the SO2 pipes and the initial aluminosilicate glass is 15 mm; the SO2 pipes are provided with a temperature control system, a flow meter and vents, the diameter of the vents is 0.2 mm, and the center distance of the vents is 12 mm. The non-tin surface of the glass faces the vents, and the initial thickness of the glass substrate is 0.6 mm.

[0074] Examples 15-16

[0075] The difference between this group of embodiments and embodiment 1 is that in the annealing step, the temperature and gradient change mode of the annealing treatment are different, as follows:

[0076] Example 15: The glass substrate is annealed by passing through a high temperature zone, a medium temperature zone and a low temperature zone at a uniform speed, wherein the temperature of the high temperature zone is reduced from 710°C to 630°C, the temperature of the medium temperature zone is reduced from 630°C to 530°C, and the temperature of the low temperature zone is reduced from 530°C to 450°C;

[0077] Example 16: The glass substrate is annealed by passing through a high temperature zone, a medium temperature zone and a low temperature zone at a uniform speed. The temperature in the high temperature zone is reduced from 680°C to 610°C, the temperature in the medium temperature zone is reduced from 610°C to 510°C, and the temperature in the low temperature zone is reduced from 510°C to 430°C.

[0078] Performance testing

[0079] The glasses provided in the above-mentioned Examples 1-12 and Comparative Examples 1-9 were used as test samples to carry out performance tests:

[0080] 1. Detection method:

[0081] (1) Use the Orihara SLP-2000 stress meter to test the stress and stress layer depth of glass;

[0082] (2) Use a two-dimensional image measuring instrument to test the glass warpage;

[0083] (3) Use a drop test machine model XH-YF1000 to perform a sandpaper drop test. The test conditions are: 180-grit sandpaper, the total weight of the test glass sample and the fixture is 186 grams, the base height is 50 cm, and the rise is 5 cm each time, once per height, until the glass breaks.

[0084] 2. Test results:

[0085] (1) The results of the investigation on the raw material ratio are shown in Table 3:

[0086] Table 3.

[0087]

[0088]

[0089] As can be seen from Table 3, due to the different raw material components of the glass, when the same annealing conditions (SO2 temperature: 30°C, flow rate: 6L / min, volume concentration: 96%) are used, the △Na2O ratio will be affected, further affecting the glass warping and strength. Especially in Comparative Examples 1-4, when the ratio of Na2O and K2O in the raw material components is too much or too little, the compressive resistance and heat resistance of the glass will be reduced, thereby affecting the glass warping; at the same time, when the ratio of MgO in the raw material components is too much, the glass will become brittle, and this brittleness may cause the glass to be more easily warped during processing or use.

[0090] (2) The results of the investigation on annealing conditions are shown in Table 4:

[0091] Table 4.

[0092]

[0093]

[0094] Combined with the first group of experimental examples, it can be seen that the temperature of SO2 during the annealing process will greatly affect the △Na2O ratio, and thus affect the glass warping. Too low (20℃) or too high (90℃) SO2 temperature is not conducive to improving glass warping. This is because the temperature has a great impact on the actual flow of SO2, causing the amount of SO2 to fluctuate greatly, resulting in a change in the amount of Na2O on the non-tin surface △ α (Na2O) and the change of tin surface△ β The ratio between the two is difficult to control precisely, resulting in uneven stress distribution between the non-tin surface and the tin surface after chemical tempering.

[0095] Combined with the second group of experimental examples, it can be seen that under the same temperature and concentration conditions, the flow rate of SO2 during annealing will also affect the △Na2O ratio, and thus affect the glass warpage. Too small (3L / min) or too large (100L / min) SO2 flow rate is not conducive to improving glass warpage.

[0096] Combined with the third group of experimental examples, it can be seen that under the same temperature and flow conditions, the concentration of SO2 during annealing will also affect the △Na2O ratio, and thus affect the glass warpage. Too small a volume fraction of SO2 (90%) is not conducive to improving the glass warpage.

[0097] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. A method for preparing high-strength and low-warpage lithium aluminosilicate glass, characterized in that: It includes: A glass substrate is obtained by a float glass forming process, the glass substrate is annealed in an atmosphere containing SO2 to obtain a lithium aluminum silicate main body glass, and the lithium aluminum silicate main body glass is chemically strengthened; During the annealing process, the volume concentration of SO2 is 96% to 100%, the outlet temperature of SO2 is 30°C to 80°C, and the change in the amount of Na2O in the non-tin surface of the aluminosilicate body glass is △ α (Na2O), the change in the amount of Na2O in the tin surface is △ β (Na2O), both satisfy: <h2 style=";text-align:left;direction:ltr">△<h2 style=";text-align:left;direction:ltr"> α <h2 style=";text-align:left;direction:ltr"> (Na2O) / △<h2 style=";text-align:left;direction:ltr"> β <h2 style=";text-align:left;direction:ltr"> (Na2O) = (1.08 = 1.28) = 1 The warpage rate of the lithium aluminosilicate glass finally obtained is less than 0.14%.

2. The method for preparing high-strength and low-warpage lithium aluminosilicate glass according to claim 1, characterized in that: During the annealing process, the non-tin surface of the aluminosilicate main glass faces the vent hole of the SO2, and the flow rate of the SO2 is 6L / min to 90L / min.

3. The method for preparing high-strength and low-warpage lithium aluminosilicate glass according to claim 2, characterized in that: During the annealing process, the distance between the aluminosilicate main glass and the vent hole of SO2 is 15-20 mm, and the diameter of the vent hole is 0.2-0.4 mm.

4. The method for preparing high-strength and low-warpage lithium aluminosilicate glass according to claim 3, characterized in that: During the annealing process, 6 to 10 SO2 ventilation pipes are arranged in the annealing kiln, each SO2 pipe is provided with a temperature control system, a flow meter and a plurality of ventilation holes, and the center distance between two adjacent ventilation holes is 12 to 18 mm.

5. The method for preparing high-strength and low-warpage lithium aluminosilicate glass according to claim 1, characterized in that: The temperature of the annealing treatment is 430°C to 710°C.

6. The method for preparing high-strength and low-warpage lithium aluminosilicate glass according to claim 5, characterized in that: During the annealing process, the temperature in the annealing furnace changes gradually in the range of 430° C. to 710° C.

7. The method for preparing high-strength and low-warpage lithium aluminosilicate glass according to claim 6, characterized in that: During the annealing process, the glass substrate passes through a high temperature zone, a medium temperature zone and a low temperature zone at a uniform speed; The initial temperature of the high temperature zone is 680-710°C and the final temperature is 610-630°C; The initial temperature of the medium temperature zone is 610-630°C, and the final temperature is 510-530°C; The initial temperature of the low temperature zone is 510-530°C, and the final temperature is 430-450°C.

8. The method for preparing high-strength, low-warpage lithium aluminosilicate glass according to any one of claims 1 to 7, characterized in that: The raw materials of the glass matrix include, by mass percentage: 61.5% to 63.2% SiO2, 19% to 20.5% Al2O3, 6.8% to 7.5% Na2O, 1.2% to 1.5% K2O, 4.2% to 4.8% Li2O, 2.6% to 3.2% MgO, 2.2% to 2.6% ZrO2.

9. The method for preparing high-strength and low-warpage lithium aluminosilicate glass according to any one of claims 1 to 7, characterized in that: The chemical strengthening is a two-step strengthening method, including: In the first chemical strengthening, the molten salt is pure NaNO3, the strengthening temperature is 430-450℃, and the strengthening time is 70-90min. For the second chemical strengthening, the molten salt is a mixed molten salt composed of 1.5-2.5wt% NaNO3 and 97.5-98.5wt%, the strengthening temperature is 410-430°C, and the strengthening time is 80-100min.

10. A high-strength, low-warpage lithium aluminosilicate glass, characterized in that: It is prepared by the preparation method described in any one of claims 1 to 9; the warpage of the lithium aluminum silicate glass is less than 0.14%, the surface CS of the lithium aluminum silicate glass is greater than 950Mpa, and the surface DOL is greater than 110μm; the intact rate of the lithium aluminum silicate glass dropped from a height of at least 160cm to the surface of 180-mesh silicon carbide sandpaper is greater than 82%.

Citation Information

Patent Citations

  • Float glass and preparation method thereof

    CN105753338A

  • Device and method for preparing TFT-LCD glass substrate by float method

    CN109867441A

  • Cover plate glass, preparation method thereof and display panel

    CN117447058A

  • Fracture-resistant lithium aluminosilicate glass and preparation method thereof

    CN118619542A